2020
DOI: 10.1002/batt.202000070
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Functional Properties of Liquid Electrolytes for Lithium‐Ion Batteries by Addition of Pyrrolidinium‐Based Ionic Liquids with Long Alkyl‐Chains

Abstract: Three ionic liquid belonging to the N-alkyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl) imides (Pyr 1 , n TFSI with n = 4,5,8) have been added as co-solvent to two commonly used electrolytes for Li-ion cells: (a) 1 M lithium hexafluorophosphate (LiPF 6) in a mixture of ethylene carbonate (EC) and linear like dimethyl carbonate (DMC) in 1 : 1 v/v and (b) 1 M lithium bis-(trifluoromethanesulfonyl)imide (LiTFSI) in EC : DMC 1 : 1 v/v. These electrolyte formulations (classified as P and T series containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…7,10 Although the ILs with short alkyl chains have low viscosity as an advantage, the ILs with long alkyl chains also present some interesting properties. [11][12][13] For example, when the IL has ions with large ionic structure in its composition, e.g., large imidazolium, ammonium and phosphonium cations, it can assume a liquid crystal function, known as ionic liquid crystal (ILC), which is able to form aggregates and crystalline phases in the liquid medium and complex structures in the solvent. 12,13 Yamanaka and co-workers have shown that the structural properties assigned to the crystalline phase are expected to suppress problems related to high viscosity, 11 but there is insufficient information about how these structures interact and affect the mixture properties and there is little literature evidence of ILCs used in aprotic ternary electrolytes for Li-metal based batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 Although the ILs with short alkyl chains have low viscosity as an advantage, the ILs with long alkyl chains also present some interesting properties. [11][12][13] For example, when the IL has ions with large ionic structure in its composition, e.g., large imidazolium, ammonium and phosphonium cations, it can assume a liquid crystal function, known as ionic liquid crystal (ILC), which is able to form aggregates and crystalline phases in the liquid medium and complex structures in the solvent. 12,13 Yamanaka and co-workers have shown that the structural properties assigned to the crystalline phase are expected to suppress problems related to high viscosity, 11 but there is insufficient information about how these structures interact and affect the mixture properties and there is little literature evidence of ILCs used in aprotic ternary electrolytes for Li-metal based batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ILs with short alkyl chains have low viscosity as an advantage, the ILs with long alkyl chains also present some interesting properties. 11–13 For example, when the IL has ions with large ionic structure in its composition, e.g. , large imidazolium, ammonium and phosphonium cations, it can assume a liquid crystal function, known as ionic liquid crystal (ILC), which is able to form aggregates and crystalline phases in the liquid medium and complex structures in the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, pyrrolidinium cations have been extensively pointed out as appropriate for use in LiBs due to their versatility, allowing combinations with different anions [20,22]. Their action has been reported to be very sensitive to changes in their lateral chains [3,[23][24][25]. However, they are not naturally electroactive, and in order to allow their use in LiBs, it is necessary to mix the ionic liquids with lithium salts [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ternary mixtures of organic solvents, ionic liquids (ILs), and Li salts have shown outstanding performance in Li-ion and Li–oxygen batteries, outperforming both binary mixtures of organic solvents or ILs with Li salt electrolytes. The binary IL-based electrolytes, despite their remarkable thermal, chemical, and electrochemical stabilities, very low vapor pressure, and nonflammability, have a high viscosity that negatively affects ion transport. On the other hand, binary electrolytes based on organic solvents exhibit better transport characteristics, but a majority of them are only stable in a narrow electrochemical potential window. A common strategy to overcome these issues is to use a combination of ILs and low-viscosity organic solvents with Li salts to form ternary mixtures. In particular, Li salts such as LiI and LiNO 3 are added to Li–air battery electrolytes to improve cyclability and provide a protective solid electrolyte layer on the anode …”
Section: Introductionmentioning
confidence: 99%